The effect of ethanolic extract and Caffeine extract of the yerba Meta plant (ilex paraguariensis) on the vital functions and tissues of the liver and kidneys in guinea pigs (Journal of Academic Research, 2024)
The active compounds contained in medicinal plants are generally the ones to which the therapeutic effect of diseases is attributed. This study aims to use the caffeine alkaloid extracted from the plant and the ethanolic extract of the yerba mate plant to know its effect on blood contents and rates of fat and vital tissues using experimental animals of the guinea pig type males, which are divided into five groups equally. The fifth group is a control group, and the first and second groups were injected with caffeine at a concentration of 10 and 20 mg/kg, respectively, and the third group was injected with yerba mate at a concentration of 200 mg/kg, while the fourth group was injected with mate at a concentration of 100 mg/kg. At the end of the experiment, blood samples were taken to examine lipid levels and blood biometrics, and organs (kidneys, liver) were removed. Transfer it to the laboratory to conduct histological examinations. It was concluded from these tests that the extract of ethanol from the Yerba mate plant at a concentration of 200 mg/kg reduces the level of cholesterol and triglycerides in the blood. It is estimated with statistical significance (P = 0.0035).